Toward a Framework for Assessing Data Quality - Carson, Carol (Washington, D.C. : International Monetary Fund, 2001)
This paper describes work in progress on data quality, an important element of greater transparency in economic policy and financial stability. Data quality is being dealt with systematically by the IMF through the development of data quality assessment frameworks complementing the IMF's Special Data Dissemination Standard (SDDS) and General Data Dissemination System (GDDS). The aim is to improve the quality of data provided by countries to the IMF; and to assess evenhandedly the quality of countries' data in Reports on the Observance of Standards and Codes. The frameworks bring together best practices including those of the United Nations Fundamental Principles of Official Statistics.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Russian Federation